Restructuring 19th Century Students’ Idea in Positivist Curriculum Using Drawings’ Analogies - A. El-Kilani, Safa (European Journal of Social Science Education and Research, 2022)
Four students’ teachers in Master Science program were subjected to instruction that aimed to master the suitable strategies in changing misconceptions. The most active and verbal student in the class had been subjected to autobiographic case study; he had been asked to write a journal including the followings: A. The most complicated idea, he believed to work as a critical barrier in understanding revolutionary type of science. B. The reason for such misunderstanding and C. The teaching strategy, he believed, to help in making successful restructuring to his concept. Student’ journal shows the followings: A. The existence of empty space between particles - moving in all directions-was the most complicated idea to be difficult to grasp; there was misunderstanding that changing in atmospheric pressure by changing latitude is due to the change in the accumulated continuous air forces that are implied on the square centimeter of flexible wall (football in this case). B. It had been indicated that such misunderstanding, on behalf of students, was due to the fact that 19th century positivists assumptions about nature of matter (that had been adapted by science educators), had led to establish instruction on discovery methods to prove those historical ideas. C. It had been pointed out that using analogies’ drawings rather than videos, to distinguish between alternative ideas and the scientific ones had helped in restructuring erroneous ideas. D. It had been pointed out that presenting a comprehensive view that takes into account all factors to explain a given phenomena, in which the pressure concept is linked to the gravity, and the atmospheric components theme, is of great importance in restructuring ideas
Keywords: case study, atmospheric pressure, positivist curriculum, misconceptions, drawings’ analogies